Historical Seismology Interdisciplinary Studies of Past and Recent Earthquakes - Fréchet, Julien; Meghraoui, Mustapha; Stucchi, Massimiliano (Modern Approaches in Solid Earth Sciences, 2008)
Modern seismology has faced new challenges in the study of earthquakes and their physical characteristics. This volume is dedicated to the use of new approaches and presents a state of the art in historical seismology. Selected historical and recent earthquakes are chosen to document and constrain related seismic parameters using updated methodologies in the macroseismic analysis, field observations of damage distribution and tectonic effects, and modelling of seismic waveforms. A critical re-evaluation of historical accounts and early seismograms provides us with the basis for a realistic seismic hazard assessment. This book is dedicated to the memory of Jean Vogt (1929 - 2005). Audience: This book is of value to seismologists, earthquake geologists, engineering seismologists, earth scientists and historians of catastrophes. .